Synthesis and photoluminescence properties of Pb2+ doped Li4CaB2O6 - BAŞAK, ALİ SADİ (ELSEVIER GMBH, 2015)
Pure and Pb2+ doped Li4CaB2O6 materials were prepared by the solid State reaction. The phase analysis of all synthesized materials were determined using the powder XRD. The synthesized materials were investigated using spectrofluorometer at room temperature. The excitation and emission bands of Li4CaB2O6:Pb2+ were observed at 263 and 298 nm, respectively. The dependence of the emission intensity on the Pb2+ concentration for the Li4CaB2O6 were studied in detail. It was observed that the concentration quenching of Pb2+ in Li4CaB2O6 is 0.01 mol. The Stokes shifts of Li4CaB2O6:Pb2+ phosphor was calculated to be 4466 cm(-1). Also, the photoluminescence properties of Pb2+ in various lithium calcium borates (LCB) with different structure was discussed. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: Inorganic borate; Luminescence; XRD; BLUE-EMITTING PHOSPHOR; LUMINESCENCE